NECROTIZING GINGIVITIS: CASE REPORTS I (REVIEW OF THE LITERATURE) - V.I. Shynkevych (Ukrainian Medical Stomatological Academy, 2015)
The prevalence of the necrotizing periodontal diseases is not high, their importance is clear because they represent the most severe conditions associated with the dental biofilm, with very rapid tissue destruction. In addition to bacteria, the etiology of necrotizing periodontal disease includes numerous factors that alter the host response and predispose to these diseases, namely HIV infection, malnutrition, stress or tobacco smoking. The diagnostic features of the disease are characteristic, but the clinical presentation may vary among patients. Successful treatment of the disease depends on systemic and local therapy choice, but requires further diagnosis of pre-existing periodontal disease and its management, as well as the leading risk factors determination and their elimination. This paper attempts to describe the clinical diagnostic features and the current treatment options along with a suggested protocol for comprehensive management with case reports and a brief review. Methods: The paper presents a clinical case report of necrotizing gingivitis: diagnosis, management and long-term results. A brief review of the paper is devoted to methods used in diagnosis and treatment. The workshop of the American Academy of Periodontology (AAP) (The 1999 AAP Classification) recognized that necrotizing ulcerative gingivitis and necrotizing ulcerative peridontitis were clinically distinguishable disease entities but were unsure if they were a part of the same disease process or were two distinct diseases. They concluded that there was insufficient data to resolve this problem, thus they decided to place both conditions in one category of "necrotizing periodontal disease". Among other acute conditions involving periodontal tissue, but not caused by oral biofilm microorganisms, there are infectious diseases, mucocutaneous disorders, allergy and traumatic injury. In most of these cases gingival involving is not severe or significant, however, these conditions are more frequent and can cause emergency visit to dentist. Certainly clinical observation would suggest that they are a part of a continuum with initial infections perhaps showing little or no clinically recognizable attachment loss despite soft tissue destruction of the papillary tissue. However, with recurrent infections, which these patients are prone to, the attachment loss becomes more apparent. Results: The clinical diagnosis of acute necrotizing ulcerative gingivitis was established in a young patient, although microscopic microbiological analysis of scrapings from the lesion did not confirm the diagnosis. Preexisting chronic generalized periodontitis was elucidated after patient`s general and local conditions were improved. The patient also had a concomitant disease of "multicolored shingles", which did not modify inflammatory periodontal disease, and recently recovered from common cold. Local secondary favorable factor for necrotizing gingivitis development was defined as chronic periodontitis; common predisposing factor was a viral disease, and the leading risk factor was recognized as tobacco smoking. Main treatment options were supragingival plaque removal and systemic antibioticotherapy with clarithromycin by 7 days. The patient was motivated to improve his oral hygiene. 5 days later, the diagnosis was changed as chronic generalized periodontitis because of appearing the opportunity of thorough periodontal examination and detection of periodontal pockets. Within dispancerization (over time dental care), the patient was strongly recommended to reduce smoking and visit dentist every 6 months for supportive periodontal therapy. Conclusions: To improve management of necrotizing periodontal diseases dentists require cooperation with physicians and internists, key personnel and medical colleagues who would help, in particular, to improve comorbid conditions in a dental patient.